Validation of the Finnish MD Anderson Dysphagia Inventory (MDADI) in patients with head and neck cancer - Ranta, Pihla; Kinnunen, Ilpo; Irjala, Heikki (Springer Science and Business Media LLC, 2025)
The aim of this study was to translate and adapt the MD Anderson Dysphagia Inventory (MDADI) questionnaire into Finnish and validate it in patients with head and neck cancer (HNC). A total of 94 participants were included: 64 dysphagic HNC patients and 30 non-dysphagic age- and gender-matched controls. The MDADI was formally translated using the forward-backward method and feasibility, test-retest reliability, internal consistency, score distribution, known-group validity, and patient feedback and were analyzed. Criterion and convergent validities were tested against the previously validated dysphagia questionnaire F-EAT-10. The results showed good variability and no floor or ceiling effects in the dysphagic group (age range 31 to 85 years, mean 67.8, SD 11.2). In all MDADI subscales, the internal consistency reliability was high (Cronbach's alpha > 0.8). Moreover, the intraclass correlation in test-retest (n = 55) was high (> 0.9) in all subscales. The MDADI was able to discriminate between dysphagic and non-dysphagic participants: the mean total score was 73.6 for the dysphagic group and 99.9 for the control group (p > 0.001). The correlations between the MDADI and the F-EAT-10 were strong demonstrating criterion and convergent validities. Patient feedback of the MDADI was positive. In conclusion, the Finnish MDADI is a valid instrument to assess dysphagia-related quality of life in patients with HNC, offering enhanced clinical and research utility.